Differential equations with derivatives in order differentiation - Антонов, В. К. (Problems of Informatization and Control, 2014)
Proposed the operation of differentiation by the differentiation order, based on the repeated use of fractional differentiation operators, and the differential equations which contain this operation. It is shown that they are reduced to ordinary differential equations. The examples of the phenomena described by differential equations with derivatives taken by the differentiation order are given